Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Komunikasi dan Hasil Belajar Bahasa Indonesia melalui Model BARAKAT pada Siswa Kelas IV SDN Karya Baru - Ilma Aulia Rahmah; Aslamiah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low levels of student activity, critical thinking skills, communication skills, and Indonesian language learning outcomes among fourth-grade students at SDN Karya Baru. Initial classroom observations showed that learning remained teacher-centered, provided limited opportunities for structured collaboration, and rarely trained students to analyze texts and communicate the reasons for their answers. This study aimed to describe teacher activity and analyze improvements in student activity, critical thinking, communication, and learning outcomes through the BARAKAT model, which integrates Problem Based Learning, Numbered Heads Together, and Talking Stick. This classroom action research was conducted in four meetings involving 15 students. Data were collected through observation and learning outcome tests and analyzed descriptively. Teacher activity increased from 19 to 32; student activity increased from 27% to 87%; critical thinking skills increased from 13% to 87%; communication skills increased from 20% to 87%; and classical learning mastery increased from 20% to 100%. These findings indicate that BARAKAT supports active and collaborative Indonesian language learning by linking problem analysis, individual accountability in groups, and equitable speaking opportunities.